Analisis klaster populasi hewan ternak di Kabupaten Nganjuk menggunakan Algoritma K-Means Clustering - Fitriyana, Vina; Bahri, Saiful (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Livestock farming has become increasingly popular in various regions, particularly among rural residents who raise different types of livestock. Nganjuk Regency, located in East Java Province, holds significant potential in the field of animal husbandry. This study aims to classify the livestock population in Nganjuk Regency using SPSS software and to identify the subdistrict with the highest livestock population. The method employed is the K-Means clustering algorithm, known for its simplicity and efficiency in clustering large datasets. The results of the study indicate that Cluster 1, categorized as having a low population, consists of 12 subdistricts. Cluster 2, categorized as having a high population, consists of 1 subdistrict, Rejoso. Cluster 3, categorized as having a medium population, consists of 7 subdistricts.